Gingival Squamous Cell Carcinoma – A Case Report (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUNDOral squamous cell carcinoma is considered to be an increasing health problem in the global public scenario. Squamous cell carcinoma is a malignant epithelial neoplasm characterized by various clinical manifestations. The most common sites are the tongue and the floor of the mouth, followed by the soft palate, gingiva, and buccal mucosa. When it occurs in gingiva, clinically it appears as an inflammatory lesion. This case report presents a case of moderately- differentiated SCC of gingiva. A 29-year-old female patient who was 5 months pregnant reported to the OPD with a 6 months history of burning sensation and painful lesion on gingiva from 34 to 37 (left molar mandibular) region. On clinical examination a proliferative lesion with purulent exudate was observed. The diagnosis of squamous cell carcinoma was made on incisional biopsy. The patient went through surgical management. Thus, gingival SCC is a condition which has better prognosis when diagnosed and managed early. Hence, dentists play an important role in early detection of gingival SCC and advising proper treatment as early as possible.